Management of inguinal hernia in premature infants: 10-year experience - Stanley John Crankson; Khalil Al Tawil; Mohammad Al Namshan; Saud Al Jadaan; Beverly Jane Baylon; Mutaz Gieballa; Ibrahim Hakim Ahmed (Journal of Indian Association of Pediatric Surgeons, 2015)
Aim: Debatable issues in the management of inguinal hernia in premature infants remain unresolved. This study reviews our experience in the management of inguinal hernia in premature infants. Materials and Methods: Retrospective chart review of premature infants with inguinal hernia from 1999 to 2009. Infants were grouped into 2: Group 1 had repair (HR) just before discharge from the neonatal intensive care unit (NICU) and Group 2 after discharge. Results: Eighty four premature infants were identified. None of 23 infants in Group 1 developed incarcerated hernia while waiting for repair. Of the 61 infants in Group 2, 47 (77%) underwent day surgery repair and 14 were admitted for repair. At repair mean postconceptional age (PCA) in Group1 was 39.5 ± 3.05 weeks. Mean PCA in Group 2 was 66.5 ± 42.73 weeks for day surgery infants and 47.03 ± 8.87 weeks for admitted infants. None of the 84 infants had an episode of postoperative apnea. Five (5.9%) infants presented subsequently with metachronous contralateral hernia and the same number of infants had hernia recurrence. Conclusions: Delaying HR in premature infants until ready for discharge from the NICU allows for repair closer to term without increasing the risk of incarceration. Because of low occurrence of metachronous hernia contralateral inguinal exploration is not justified. Day surgery HR can be performed in former premature infant if PCA is >47 weeks without increasing postoperative complications.